“Organización estructural y funcional para la Cooperativa de Transportes de Pasajeros en Buses y Busetas Río San Pablo del cantón La Maná, provincia de Cotopaxi, Año 2021”. - Chapman Barrios, Cristian Eduardo (2021)
The research project carried out has as general objective, to establish a structural and functional organization model for the Cooperativa de transporte de pasajeros en autobuses y busetas Río San Pablo in La Maná canton, Cotopaxi province in 2021, to improve its organizational and functional performance, which arose from the problem of the lack of an organizational structure in the company. The research allowed us to know the functions performed by the Cooperative's collaborators, in order to establish responsibilities so that the activities can be carried out correctly and avoid duplications. In order to fulfill this purpose, descriptive research was used because it allowed us to understand the characteristics of the problem, explanatory research because it helped us to identify the causes and effects of the problem presented in the cooperative, field research because we were able to obtain the information in the exact place and time in which things occur and bibliographic research to support the theoretical basis of our research, among the methods used were the inductive, deductive and synthetic analytical method, the research techniques used were observation, interview and survey and the research instruments were questionnaires. The research was based on a total population of 66 people, including the manager, members and collaborators. This information was obtained through a previous interview with the cooperative's manager; surveys were applied to the members and collaborators. The results of the research carried out with the partners and collaborators of the Cooperativa de transporte de pasajeros en autobuses y busetas Río San Pablo indicate that their collaborators are not informed about the functions and responsibilities that they must perform, because the cooperative does not have a manual of functions. Therefore, our proposal is oriented to the elaboration of an organizational chart for the cooperative and a functions manual, thus allowing for the improvement of processes, policies and institutional performance.